Reconstructing Legal Certainty in Indonesia from the Perspective of Siyāsah Syar‘iyyah: From Legal Formalism to Substantive Justice - Sutarja Sutarja; Holijah Holijah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Legal certainty constitutes one of the fundamental pillars of a state governed by the rule of law, serving to ensure order, justice, and the protection of citizens’ rights. However, the implementation of law in Indonesia continues to face various challenges, including overlapping regulations, inconsistencies in law enforcement, disparities in judicial decisions, and a tendency toward legal formalism that often neglects the public sense of justice. This article aims to analyze the problems of legal certainty in Indonesia and to propose a reconstruction of the concept of legal certainty from the perspective of Siyāsah Syar’iyyah. This research employs a normative legal research method using conceptual, statutory, and philosophical approaches. The sources of data include legislation, constitutional law literature, Islamic legal scholarship, and relevant scientific journal articles. Data were collected through library research and analyzed using qualitative methods with deductive-inductive reasoning. The findings indicate that the paradigm of legal certainty in Indonesia remains predominantly influenced by a positivistic approach that views law merely as a body of written norms. From the perspective of Siyāsah Syar’iyyah, legal certainty is not only understood as compliance with legal texts but also as an instrument for realizing substantive justice for all citizens. The reconstruction of legal certainty should therefore be directed toward the integration of legality, justice, and public welfare (maslahah) through the development of responsive regulations, the strengthening of the integrity of law enforcement institutions, the harmonization of legislation, and the implementation of the principles of Maqāṣid al-Sharī‘ah in both the legislative process and law enforcement practices